The Efficacy Of Glass Ionomer Hybrid As Orthodontic Brackets Adhesives To Inhibit Calsium Released Of The Enamel - Rina Sutjiati (Universitas Muhammadiyah Yogyakarta, 2012)
Composite resins are predominantly used to bond orthodontic brackets onto teeth. These can lead to calcium released of the enamel surrounding the brackets. Purpose : To observe calcium release during the use of adhesives which release fluoride Method : This experimental study was design to determine the calcium released after soaking in the acid solution. This in vitro study used forty extracted human premolars (20 teeth were bonded with glass ionomer, and 20 teeth were bonded with glass ionomer hybrid). Half of the teeth in each group were treated with fluoride application and the other half were not treated fluoride application topically. Calcium released of the enamel was evaluated using Spectrofotometer. Result :The results showed that there was a significant difference between glass ionomer group without and with fluoride application (p0,005), and there was not significant difference (p0,005) in the group of glass ionomer hybrid without and with fluoride application topically. Conclusion :The adhesive glass ionomer hybrid could prevent calcium released with or without the usage of sodium fluoride.